Supramolecular Liquid Crystalline Polymers and Networks : Incorporating Flexible Networking Agents in Mesophase Formation and Stability - Thurber, Charles A. (My University, 2013)
Previous work on controlled thermoreversible mesogenic networks has shown that there is a direct link between functionality of the crosslinking agent and clearing compositions. The purpose of this study was to involve the synthesis of crosslinking agents of multiple functionalities with the hydrogen bond acceptor being separated from the central atom by symmetric extended aliphatic chains.
Color poster with text, diagrams, graphs, images, and tables.
Keywords: Supramolecular chemistry; Liquid crystals--Research; Polymeric composites; Hydrogen bonding--Research; Posters